2014
DOI: 10.1159/000358326
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Cell-Free DNA in Maternal Blood in Screening for Aneuploidies: Meta-Analysis

Abstract: Objective: To review clinical validation or implementation studies of maternal blood cell-free (cf) DNA analysis in screening for aneuploidies and to explore the potential use of this method in clinical practice. Methods: Searches of PubMed and MEDLINE were performed to identify all peer-reviewed articles on cfDNA testing in screening for aneuploidies between 2011, when the first such study was published, and 20 December 2013. Results: Weighted pooled detection rates (DR) and false-positive rates (FPR) in sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
155
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(161 citation statements)
references
References 72 publications
4
155
0
2
Order By: Relevance
“…No pregnancies were terminated after abnormal NIPT without confirmation in chorionic villi or amniotic fluid cells. Detection rates (DR) for the common trisomies (96% for trisomy 21, 100% for trisomies 13 and 18) and false positive rates (0.14% for trisomies 21 and 13, 0.07% for trisomy 18) were comparable to previous studies 12. Our data support introduction of NIPT as a safe second‐tier screening test to accurately select the small proportion of women truly at high risk for fetal trisomy, and to reliably reassure all others.…”
Section: Discussionsupporting
confidence: 81%
“…No pregnancies were terminated after abnormal NIPT without confirmation in chorionic villi or amniotic fluid cells. Detection rates (DR) for the common trisomies (96% for trisomy 21, 100% for trisomies 13 and 18) and false positive rates (0.14% for trisomies 21 and 13, 0.07% for trisomy 18) were comparable to previous studies 12. Our data support introduction of NIPT as a safe second‐tier screening test to accurately select the small proportion of women truly at high risk for fetal trisomy, and to reliably reassure all others.…”
Section: Discussionsupporting
confidence: 81%
“…cffDNA is NOT an alternative to first trimester screening that can easily pick up structural abnormalities which are more common than chromosomal abnormalities [1,3,5]. The advantages of early diagnosis of a structural abnormality in terms of patient counseling and ease of early termination (in case the abnormality warrants it) cannot be over emphasized.…”
Section: Dear Editorsmentioning
confidence: 99%
“…Women with very high risk (C1:10) should be offered invasive testing, whereas women with intermediate risk (1:11-1:2500) should be offered cffDNA. This policy would require cfDNA for 1/4th of the screened population and detect 98 % of trisomies at an invasive rate of only 0.8 % [5].…”
Section: Dear Editorsmentioning
confidence: 99%
“…For trisomy 21, individual studies showed the detection rate (DR) ranges between 94.4% and 100%, and false positive rates (FPR) ranges between 0 and 2.1% [9]. Fairly good results have been demonstrated for detection of trisomy 18, while screening for trisomy 13 and monosomy X has a poorer performance due to the highly variable amplification of these chromosomes with lower guanosine and cytosine content.…”
mentioning
confidence: 99%
“…Use of NIPT has been proposed for use as either screening for the general obstetric population or as a contingent screening test in high-risk groups. The first option would be quite expensive given the sheer volume of tests performed and the subsequent invasive testing required for positive cases (number of false positives expected is about 1%) [9]. However, this option would maximize the prenatal detection rate (99%).…”
mentioning
confidence: 99%